(untitled) (Research, Society and Development, 2022)
Analyze the application of screening as a contagion containment toll of SARS-COV-2 virus in hemodialysis patients. Descriptive observational study was done in a hemodialysis clinical at São Paulo state (Brazil), during March 2020 to May 2021. A survey of the World Health Organization and the Ministry of Health guidelines and the strategies adopted to face the COVID-19 pandemic was carried out. The team of collaborators developed and implemented a screening process at the clinic. This study evaluated patients in hemodialysis program (n=65) and multidisciplinary collaborators team (n=51). After surveying the strategies to be adopted by collaborators to fight the pandemic, a screening process was created aiming at the flow of patient care. This process provided training for collaborators, in addition to separating care for patients with and without flu signs and symptoms. Of the patients, 15.4% (n=10) had confirmation of SARS-COV-2 contamination by RT-PCR. Only 1 patient evolves to death, with no covid-related cause. Among collaborators team, 15.7% (n=8) confirmed contamination with the virus. Of these, only 1 possibly had contamination during infected patient care. In this study, it can be concluded that the implementation of the screening process provided to hemodialysis patients, with and without flu-like symptoms, a more effective care, as well as a safer environment for the entire collaborator team and for the patients.